The Influence of E-Commerce, Digital Payments, and Digital Literacy on MSME Income in The Perspective of Islamic Economics - Alwi Rifa'i; Nurbaiti Nurbaiti; Muhammad Lathief Ilhamy Nasution (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The rapid advancement of digital technologies has transformed business landscapes, offering micro, small, and medium enterprises (MSMEs) unprecedented opportunities to enhance competitiveness and income. In Muslim-majority contexts, such as Medan Johor, this transformation must align with Islamic economic principles to ensure both economic and ethical value creation. This study employs a quantitative survey of 98 MSME actors, measuring the effects of e-commerce, digital payment, and digital literacy on income. Using multiple linear regression, the results demonstrate that all three variables exert a positive and significant impact, with digital literacy emerging as the most influential driver of effective technology adoption. These findings resonate with Islamic economic principles of maslahah (public benefit), efficiency, and the prohibition of gharar (excessive uncertainty), which emphasize transparency, utility, and blessings in economic transactions. The study extends existing literature by embedding Islamic economic perspectives within the MSME digitalization discourse and by capturing the socio-religious nuances of a localized setting. Policy implications include fostering Shariah-compliant digital literacy programs, strengthening regulatory frameworks, and enhancing the role of Islamic financial institutions in delivering technology-based, Shariah-compliant financing solutions to empower MSMEs sustainably.